Antioxidant, Antimicrobial, and Protein Kinase Inhibition Profiling of C. ambrosioides Seed Extracts along with RP-HPLC - Saira Bano; Muhammad Waleed Baig; Mohammad K. Okla; Syeda Saniya Zahra; Nosheen Akhtar; Wahidah H. Al-Qahtani; Hamada AbdElgawad; Ihsan-Ul Haq (Journal of Chemistry)
The validation of underexplored traditional plant remedies represents a reservoir of novel leads for drug discovery. In line with this, in vitro total phenolics and flavonoids content, multimode antioxidants, antimicrobial, cytotoxicity, and protein kinase inhibition assays were conducted on C. ambrosioides seed extracts in addition to RP-HPLC. Methanol extract exhibited highest total phenolics (64.6±0.6 μg gallic acid equivalent/mg) and flavonoids (50.9±0.5 μg quercetin equivalent/mg) content. RP-HPLC quantified rutin (1.98 μg/mg) in methanol extract whereas quercetin (0.322 μg/mg) and kaempferol (2.86 μg/mg) in methanol-distilled water extract. Methanol extract exhibited highest ascorbic acid equivalent (AAE) free radical (DPPH) scavenging (IC50 of 110.7±5 μg/ml), total antioxidant capacity (110.6±2.2 μg AAE/mg), and total reducing power (94.30±0.46 μg AAE/mg). Highest antibacterial activity against K. pneumonia (14±1.61 mm ZOI) and antifungal activity against F. solani (17±1.38 mm ZOI) were shown by n-hexane and chloroform extracts, respectively. Ethyl acetate extract exhibited highest brine shrimps cytotoxicity (LC50 of 125 μg/ml). A noteworthy protein kinase inhibitory potential was shown by ethanol extract with a 20±1.27 mm bald zone. Therapeutic potential of medicinal plants can be completely explored by using multiple solvent system. This study makes C. ambrosioides, a resourceful prospect for the bioactivity-guided isolation of lead compounds.